VEGFA GENE variation influences hallucinations and frontotemporal morphology in psychotic disorders: a B-SNIP study - Lizano, Paulo (Transl Psychiatry, 2018)
Vascular endothelial growth factor A (VEGFA) dysfunction may contribute to a number of pathological processes that characterize psychotic disorders. However, the influence of VEGFA gene variants on clinical and neuroimaging phenotypes in psychotic disorders has yet to be shown. In the present study, we examined whether different VEGFA gene variants influence psychosis risk, symptom severity, cognition, and brain volume. The study group included 480 probands (Bipolar I disorder with psychosis, n = 205; Schizoaffective disorder, n = 112; Schizophrenia, n = 163) and 126 healthy controls that were recruited across six sites in the B-SNIP consortium. VEGFA variants identified for analysis (rs699947, rs833070, and rs2146323) were quantified via SNP chip array. We assessed symptoms and cognition using standardized clinical and neuropsychological batteries. The dorsolateral prefrontal cortex (DLPFC), medial temporal lobe, and hippocampal volumes were quantified using FreeSurfer. In our sample, VEGFA rs2146323 A- carriers showed reduced odds of being a proband (p = 0.037, OR = 0.65, 95% CI = 0.43–0.98) compared to noncarriers, but not for rs699947 or rs833070. In probands, rs2146323 A- carriers demonstrated fewer hallucinations (p = 0.035, Cohen’s d = 0.194), as well as significantly greater DLPFC (p < 0.05, Cohen’s d = −0.21) and parahippocampal volumes (p < 0.01, Cohen’s d = −0.27). No clinical or neuroimaging associations were identified for rs699947 or rs833070. In general, we found that the three SNPs exhibited several significant negative relationships between psychosis symptoms and brain structure. In the probands and control groups, positive relationships were identified between several cognitive and brain volume measures. The findings suggest VEGFA effects in the DLPFC and hippocampus found in animals may also extend to humans. VEGFA variations may have important implications in identifying dimensional moderators of function that could be targeted through VEGFA-mediated interventions.